Folic acid supplementation in pregnancy to prevent preterm birth: a systematic review and meta-analysis of randomized controlled trials. (April 2016) - Saccone, Gabriele; Berghella, Vincenzo
Abstract: Folic acid (FA) may have a role in the prevention of pregnancy complications. However, the efficacy of FA supplementation in reducing the risk of preterm birth (PTB) is still unclear. The aim of this systematic review with meta-analysis was to evaluate the efficacy of folic acid supplementation during pregnancy to prevent preterm birth (PTB). The research protocol was designed a priori, defining methods for searching the literature in electronic databases, including and examining articles, and extracting and analyzing data. We included all randomized trials (RCTs) of asymptomatic singleton gestations without prior PTB who were randomized to prophylactic treatment with either FA supplementation or control (placebo or no treatment). The primary outcome was the incidence of PTB <37 weeks. Five randomized trials including 5, 332 asymptomatic singleton gestations without prior PTB were included in the analysis. Women who received FA supplementation had a similar rate of PTB <37 weeks (22.6% vs 22.9%; RR 0.99, 95% CI 0.82−1.18), PTB < 34 weeks (7.1% vs 8.7%; RR 0.77, 95% CI 0.55−1.09) and of preterm premature rupture of membranes (2.4% vs 2.9%; RR 0.81, 95% CI 0.44−1.50) compared with control group. Regarding neonatal outcome we found no significant differences in birth weight (mean difference 85.58 g, 95% CI -55.17−226.34), low birth weight (21.0% vs 15.1%; RR 0.79, 95% CI 0.49 to 1.28) and perinatal death (2.9% vs 2.4%; RR 0.90, 95% CI 0.60−1.34). In summary, FA supplementation during pregnancy does not prevent PTB <37 weeks. Daily FA supplementation remains the most important intervention to reduce the risk of neural tube defects.